Evaluation of Pakistani wheat germplasm for leaf rust resistance at various locations. - Sabina Asghar; Aziz Ur Rehman; Nadeem Ahmad; Sadia Ajmal; Aneela Ahsan; Saima Gulnaz; Makky Javed; Javed Ahmad; Javed Iqbal; Sumera Bibi; Sajid Fiaz; Basem H Elesawy; et al. (PLoS ONE, 2022)
341 entries comprising of 250 genotypes/lines and 91 gene differentials were tested for leaf rust (Puccinia triticina Erik) in different ecological zones of Punjab during 2016-17 and 2017-18. Each entry was planted in a single 1 m long row and Morocco was used as a spreader. Data on leaf rust severity was recorded once in 3rd week of March during both study years at all locations by following Modified Cobb Scale while the data was recorded three times on 2nd, 22nd and 29th March during 2018 at Faisalabad location to study rust development pattern. The disease severity ranged from 0-100S during 2016-17 and from 0-80S during 2017-18. The genotype HYT 60-5 and the genes Lr-19, Lr-26 and Lr 27+31 showed no disease symptoms at any location during both the study years. These genes can be used for future breeding material development. Area under disease progressive curve (AUDPC), calculated on the basis of periodical readings from Faisalabad, ranged from 0-550 and the susceptible check Morocco has AUDPC value of 600. 120 entries including HYT 60-5 have disease progression 0, which showed that there may be a major gene based resistance in these entries. Area under disease progressive curve/Day (AUDPC/DAY) was calculated for the rest of 130 genotypes to have an understanding of the disease progression pattern and out of which 43 entries have AUDPC/Day value ranging from 1-2 and 28 entries have AUDPC/Day value ranging from 2-3 which revealed that these entries are very useful for use in breeding for durable rust resistance and can be utilized as a parent in back cross and top cross breeding schemes. Material with AUDPC value less than 10 is the best source of resistance against the leaf rust. Varieties/advanced lines, Ujala-16, V-14154, and V-14124 have shown slow rust development and are very good sources of resistance. Similarly, HYT 60-5 has proven an excellent source of resistance. The advance line V-14154 has been approved as a commercial cultivar by the name "Akbar-19".